The Effectiveness of Learning Methods by Measuring Accuracy and Rationality in Prescription Writing by Medical Students - Bagas Widiyanto; Muhamad Riza (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Writing prescriptions accurately and rationally is a competency that must be achieved by medical students during medical education. This capability includes detailed knowledge of the components of the recipe and details of the components of the drug. This study aims to determine the description of the prescription writing practicum learning method carried out in the Pharmacology section of Faculty of Medicine in Unissula.Subjects and Method: This research is a descriptive study by looking at the prettest and posttest values. It was conducted in March 2020. The subjects of this study were 159 students who were registered participants of the psychiatry module in semester 6 in the undergraduate medical education study program at Faculty of Medicine in Unissula. 159 students were randomly divided into 20 SGD (Small Group Discussion), batch 1 SGD 1-10 and SGD 11-20 in batch 2. Each batch carried out practicum for 100 minutes. The activity begins with a pretest / giving case scenarios, then the discussion and discussion session ends with a posttest. The data in this study are numerical data and analyzed descriptively.Results: The results of the study indicated that the improvement across categories and those assessed was both the detailed component of the recipe and the detail component of the drug. The detail component of the prescription had the highest score increase in the patient name category by 27% higher posttest than pretest. In the detail component of the prescription, there was the highest increase in the category of Sedian Medicine (BSO) by 20.7% and that was a higher posttest value when compared to the pretest value.Conclusion: Clinical-based special learning methods with small class discussions are needed in an effort to improve the ability to write prescriptions appropriately and rationally by adjusting the level of education years.Keywords: prescription, rational, medical studentCorrespondence: Bagas Widiyanto. Department of Pharmacology, Faculty of Medicine, Universitas Islam Sultan Agung. Jl. Raya Kaligawe KM. 4, Semarang 1054, Ccentral Java, Indonesia. Email: bagaswidiyanto@unissula.ac.idJournal of Health Policy and Management (2021), 06(01): 74-80https://doi.org/10.26911/thejhpm.2021.06.01.08